2016
DOI: 10.1007/s00330-016-4319-1
|View full text |Cite
|
Sign up to set email alerts
|

CT colonography for surveillance of patients with colorectal cancer: Systematic review and meta-analysis of diagnostic efficacy

Abstract: • CT colonography compares favourably to colonoscopy/standard CT for colorectal cancer surveillance. • CT colonography offers single-test luminal, serosal and extra-colonic assessment. • CT colonography is a potentially cost-saving alternative to standard surveillance protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
0
17
1
2
Order By: Relevance
“…14 A recent meta-analysis looking at additional CTC studies showed excellent pooled sensitivity for detecting both local cancer recurrence (95%) and metachronous cancers (100%). 13 Specificity for anastomotic cancer in this meta-analysis was reported to be 100%. However, specificity for anastomotic cancer recurrence may not reflect the actual OC referral rate from CTC related to abnormal focal findings at the anastomosis.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…14 A recent meta-analysis looking at additional CTC studies showed excellent pooled sensitivity for detecting both local cancer recurrence (95%) and metachronous cancers (100%). 13 Specificity for anastomotic cancer in this meta-analysis was reported to be 100%. However, specificity for anastomotic cancer recurrence may not reflect the actual OC referral rate from CTC related to abnormal focal findings at the anastomosis.…”
Section: Discussionmentioning
confidence: 68%
“…Since standard CT is common to both arms, either approach can likely detect extraluminal peri-anastomotic recurrence, although the CT-CTC combination may have some advantages in this regard. Although prior retrospective studies have shown that CTC is highly sensitive for detecting anastomotic and peri-anastomotic cancer recurrence, 13 the rate of potential CTC false-positives leading to unnecessary OC referral (with associated increased costs) is less certain. 4 This is perhaps of greatest relevance in relatively low-risk post-surgical cohorts without clinical evidence of recurrent disease.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…El diagnóstico de las neoplasias sincrónicas de nuestra muestra, fueron todos ellos confirmados tras la intervención quirúrgica con un 100% de sensibilidad para su detección, como los hallazgos publicados por Park et al 140 en el 2012 y reforzados por los hallazgos de Porté et al 141 en el 2017, donde afirma así como otros autores que la CV es actualmente la única prueba diagnóstica alternativa a la colonoscopia óptica incompleta, por este motivo.…”
Section: Grupo De "Co Incompleta"unclassified